Improving Conservative Treatment of Chronic Rhinitis - Qosim o'g'li, Yo'ldoshov Elchinbek; A. A., Khayitov (Journal of Science in Medicine and Life, 2025)
Chronic rhinitis is an inflammatory process that affects the patient's nasal mucosa. The disorder develops against the background of infectious, allergic, toxic and other factors. There are many forms of the disease (some classifications include dozens of varieties of the pathological condition). Each of them requires a specific approach to therapy. The disorder is accompanied by serious disorders in nasal breathing, which are transient or permanent. Depending on the clinical situation. Symptoms of the pathological process are nasal discharge, impaired sense of smell, etc. In the absence of adequate therapy, the disease leads to many complications. Including dangerous (respiratory tract, heart). Examination and treatment is the work of an ENT doctor, an otorhinolaryngologist.